Distribusi Ruang Insektisida Heptaklor di Lahan Pertanian Kabupaten Bantul Provinsi Daerah Istimewa Yogyakarta - Sigit Yuli Jatmiko; Edhi Martono; Djoko Prajitno; Suratman Worosuprojo (Universitas Gadjah Mada, 2010)
Heptachlor (C10H5Cl7) was an organochlorine insecticide compound, which was considered POPs (Persistent Organic Pollutants) that is highly toxic to human. Since 2007 heptachlor insecticide was banned in Indonesia because of its chronic toxicity, persistency, bioaccumulative, and carcinogenic natures. But its illegal use is still rampant because its dark market availability, cheap price, and is effective in eradicating the pest. Furthermore, there is also lack of assertiveness of regulations and applicable laws. The objectives of the research were to identify pollution, pollution level, spatial distribution, and its correlation with soil chemicals properties, as well as the risks to health caused by heptachlor use. Research was conducted in 2010 by a survey on agricultural land in the regency of Bantul, Province of Yogyakarta Special Region on a 144 point grids. The tool used to determine heptachlor residue was GC-MS chromatography using Shimadzu GC-2014. The analysis showed that heptachlor was detected in soil, water and in agricultural products. Heptachlor residues were detected in 137 locations (95%) of 144 agricultural land sites, and the water residues on 11 sites exceeded the levels set according to levels of Government Regulation No. 82 of 2001. Heptachlor residue levels in agricultural products (rice, corn, soybeans, green beans, peanuts, and shallot) exceeded the maximum residue limit (MRL) established by the ISO (7313:2008). Soil acidity (pH) has very significant effect on the process of dissipation (loss) of heptachlor (p <0.01) in the soil. Based on the rules of Cambardella distribution, it was discovered that heptachlor had spatial autocorrelation with nugget-sill ratio of 35.7%. Heptachlor polluted rice in 37 locations with hazard index values >1.